IDENTIFIKASI SIFAT KIMIA TANAH DAN TINGKAT KESUBURAN TANAH PADA LAHAN BERA DI DESA WOLOKELO KECAMATAN KELIMUTU KABUPATEN ENDE - Fransiskus Tobias Udu; Imaculta Fatima; Charly Mutiara (Agrica: Journal of Sustainable Dryland Agriculture, 2022)
The fallow system is a system of restoring soil fertility by leaving the soil uncultivated. Almost all traditional farming systems practice the fallow system. This study aims to determine the chemical properties of the soil and the level of soil fertility on Bera land in Wolokelo Village. Research with this exploratory method, sampling the soil on the vegetable field without using the fallow period, the fallow period is 5 years and the fallow period is 10 years. The study was conducted from July to October 2020. The variables observed were soil pH, C-Organic, P2O5, K2O, CEC, and KB. The variables that have been analyzed are described by comparing the criteria for soil chemistry and soil fertility from the Bogor Soil Research Center. The results showed that the chemical properties of soil on fallow and non-fallow horticultural lands for C-organic soil elements were 4.50% -4.12%, total soil N ranged from 0.76%-0.72%, soil P ranged from 0.76% to 0.72%. between 77.18-72.20, the K element in the soil in Wolokelo Village ranged from 1.06-1.09 me/100g, the CEC element ranged from 39.27-33.77me/100g, the soil KB ranged from 80.87 %-80.31%, and soil pH ranged from 6.15-6.08. While the criteria for soil fertility on fallow land in Wolokelo Village are classified as moderate.